Potensi Antioksidan Biji Pepaya terhadap Parameter Oksidatif Jantung pada Tikus Jantan Model Diet Tinggi Lemak: Antioxidant Potential of Papaya Seeds on Cardiac Oxidative Parameters in Male Rats with High Fat Diet Model - Arif Santoso; Choirul Huda; Sulastri; Pera Amelia; Rissa Laila Vifta; Melati Aprilliana Ramadhani; Eka Noviya Fuzianingsih (Indonesian Journal of Pharmacy and Natural Product, 2025)
An imbalance between the body's antioxidant system capacity and free radical production can lead to oxidative stress, which ultimately causes the lipid peroxidation process. This phenomenon is commonly identified by increased superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) concentrations. The objective of this study was to assess the efficacy of ethanolic papaya seed (Carica papaya L.) extract in modulating SOD and MDA levels in the heart tissue of male Sprague-Dawley rats subjected to a high-fat diet over 17 days. A total of 30 rats were used and allocated into six groups: a positive control (K+), a negative control (K−), a standard control (KN), and three treatment arms receiving oral doses of 150 mg/kgBW (P1), 250 mg/kgBW (P2), and 350 mg/kgBW (P3). The extraction process employed 70% ethanol through maceration. The lowest MDA average was recorded in the P3 group (3.50±1.65), whereas the K-group exhibited the highest level (24.45±4.71). In terms of SOD, the K+ group had the highest mean (65.46±5.93), and the K− group the lowest (36.34±7.57). Statistical analysis using Tukey’s test showed that administration of 350 mg/kg body weight extract yielded results closely resembling those of the positive control. However, the observed differences did not reach statistical significance (p > 0.05). The conclusion is that administration of papaya seed extract at a dose of 350 mg/kgBW has the potential to reduce MDA levels and increase SOD levels, with effects similar to positive controls.   ABSTRAK Tidak seimbangnya antara kapasitas sistem antioksidan tubuh dan produksi radikal bebas dapat mengakibatkan kearah stres oksidatif, yang pada akhirnya menyebabkan proses peroksidasi lipid. Keadaan ini ditandai oleh aktivitas enzim superoxide dismutase (SOD) yang meningkat dan konsentrasi malondialdehida (MDA) yang menurun. Penelitian ini bertujuan mengevaluasi potensi ekstrak etanol biji pepaya (Carica papaya L.) dalam memodulasi kadar SOD dan MDA pada jaringan jantung tikus jantan galur Sprague Dawley yang diberi diet tinggi lemak pada rentang waktu 17 hari. Penelitian ini memakai desain eksperimental dengan melibatkan 30 ekor tikus, yang dikelompokkan menjadi enam: kelompok kontrol positif (K+), kontrol negatif (K−), kontrol normal (KN), serta tiga kelompok perlakuan dengan dosis bertingkat yaitu 150 mg/kgBB (P1), 250 mg/kgBB (P2), dan 350 mg/kgBB (P3). Ekstrak diperoleh melalui metode maserasi menggunakan pelarut etanol 70%. Hasil analisis menyatakan bahwa kadar MDA terendah ditemukan pada kelompok P3 (3,50±1,65), sedangkan kadar tertinggi terdapat pada kelompok K− (24,45±4,71). Sebaliknya, kadar SOD tertinggi dicatat pada kelompok K+ (65,46±5,93) dan terendah pada kelompok K− (36,34±7,57). Berdasarkan uji lanjut Tukey, pemberian ekstrak biji pepaya dosis 350 mg/kgBB (P3) memberikan hasil yang secara statistik mendekati kelompok kontrol positif, meskipun belum menyatakan perbedaan bermakna (p > 0,05). Kesimpulannya adalah pemberian ekstrak biji pepaya dosis 350 mg/kgBB memiliki potensi pada penurunan kadar MDA dan meningkatkan kadar SOD, dengan efek yang menyerupai kontrol positif.